Effect of biocontrol agents on production of rooted back pepper cutting in serpentine method - R Pervez, A I Bhat, V Srinivasan, R S Bhai, K P Subila, S J Eapen, A Reshma, (Journal of Spices and Aromatic Crops, 2018)
Availability of disease free quality planting material is a major limiting factor in black pepper cultivation. In order to meet the increasing demand and also to create awareness on good agricultural practices for healthy disease free planting material production to farmers, a nursery experiment was started with improved varieties of black pepper by adopting a non-chemical bio-intensive management strategy. Here solarization of potting mixture was the main concern followed my amending the solarized potting mixture with potential bioagents. The experiment was designed in a two factor CRD with four improved varieties and five treatments. Each treatment contains a combination of two bioagents with antifungal and nematicidal properties respectively. The common recommended fungicide Metalaxyl-Mancozeb (0.125%) and nematicide carbsosulfan (0.1%) was used as control. The treatments were incorporated individually into solarized potting mixture and planted with improved varieties used viz., IISR Girimunda, Malabar Excel, Shakti and Thevam, The plants in each treatment were kept for multiplication by serpentine method with proper irrigation and phytosanitation. The results of plant growth and establishment in different treatments, showed that fortification of solarized potting mixture with Trichoderma harzianum + Pochonia chlamydosporia combination or combination of Streptomyces strains (Act 2+9) are significantly superior (35.46% and 21% respectively) for the production of healthy rooted planting material. IISR Malabar Excel and IISR Thevam produced the maximum number of plants from a single node cutting in treatment with T. harzianum + P. chlamydosporia (T1) (59 nos. and 51 nos. respectively) followed by Malabar Excel with Act 2+9 and Act 5+9 (45 nos. each). So an average of 6-7 plants/month/cutting was produced in the potential treatment while it was only 3-4 plants in control. The advantage of the method is that, after solarization and fortification with respective bioagents, there is no need for further application of any fungicides, insecticides or any other nutrient spray as usually done. Thus the method of soil solarization followed by fortification of either T. harzianum+ P. chlamydosporia or combination of Streptomyces strains viz., Ketasatospora setae (Act 2) and S. tauricus (Act9) is found suitable for the production of healthy quality planting material of high yielding varieties to meet the increasing demand of planting material with a C:B ratio of 1:2.